Multimodality imaging in arrhythmogenic cardiomyopathy - Laura Tapoi; Alexandra Clement; Rodica Radu; Radu Sascau (Sciendo, 2021)
Arrhythmogenic cardiomyopathy, as it has been recently redefined, is characterized by progressive myocyte loss with fibrosis and fat infiltration of the myocardium, which finally leads to a broad clinical spectrum ranging from heart failure symptoms to sudden cardiac death. The diagnosis of arrhythmogenic cardiomyopathy is challenging particularly because of its heterogeneity in presentation, which varies from focal right ventricular involvement to biventricular or prominent left ventricular phenotype. In the past decades, the development of new electrocardiographic and imaging diagnostic criteria for arrhythmogenic cardiomyopathy constituted an important area of research and resulted in the elaboration of the Padua criteria. However, even with the widespread availability of modern imaging techniques, there is still a lack of awareness in the health care community and this pathology persist in being under-or misdiagnosed. Given the limited indication of endomyocardial biopsy for the diagnosis of arrhythmogenic cardiomyopathy, one can conclude that the progress that has been made in the last few years in the multimodality imaging field is of utmost importance for the early detection and proper treatment of patients with arrhythmogenic cardiomyopathy, providing valuable prognostic information.